1997
DOI: 10.1002/chem.19970031007
|View full text |Cite
|
Sign up to set email alerts
|

The Versatility of Lithium Reagents in Synthetic Organometallic Chemistry: Their differing reactions with [Cp*Mo(NO)(CH2SiMe3)2]

Abstract: [Cp*Mo(NO) (CH,SiMe,),] exhibits three principal types of reaction with the various lithium reagents investigated during this study, namely: regioselective deprotonation, reduction, and addition. Deprotonation of the reactant, achieved by treatment with lithium amide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The physical properties of solid 4 are similar to those of monomethyl 1 , but contrast with the established trend generally associated with this class of bis(alkyl) complexes. For example, the monomeric complexes Cp*Mo(NO)R 2 (R = CH 2 SiMe 3 , CH 2 CMe 3 , CH 2 CMe 2 Ph) are red-purple crystalline solids which dissolve readily in all common organic solvents to form intensely purple solutions. , In contrast, solid 4 is a pale-yellow microcrystalline powder that is sparingly soluble in alkane solvents and Et 2 O and dissolves readily only in CH 2 Cl 2 and CHCl 3 , producing intensely purple solutions. A dimeric formulation for solid 4 is indicated by an intense peak at m / z = 583 in its MALDI TOF spectrum, but EI and FAB experiments reveal only the presence of monomeric 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The physical properties of solid 4 are similar to those of monomethyl 1 , but contrast with the established trend generally associated with this class of bis(alkyl) complexes. For example, the monomeric complexes Cp*Mo(NO)R 2 (R = CH 2 SiMe 3 , CH 2 CMe 3 , CH 2 CMe 2 Ph) are red-purple crystalline solids which dissolve readily in all common organic solvents to form intensely purple solutions. , In contrast, solid 4 is a pale-yellow microcrystalline powder that is sparingly soluble in alkane solvents and Et 2 O and dissolves readily only in CH 2 Cl 2 and CHCl 3 , producing intensely purple solutions. A dimeric formulation for solid 4 is indicated by an intense peak at m / z = 583 in its MALDI TOF spectrum, but EI and FAB experiments reveal only the presence of monomeric 4 .…”
Section: Resultsmentioning
confidence: 99%
“…We have an abiding interest in the series of 16e, d 4 metallonitrosyl complexes of general formula Cp‘M(NO)R 2 (Cp‘ = η 5 -C 5 H 5 (Cp), η 5 -C 5 Me 5 (Cp*); M = Mo, W; R = −alkyl, aryl), and we continue to explore their rich and diverse chemistry . During our investigations, we have established that the Lewis-acid character of these compounds is due to the π-acidic nitrosyl ligand stabilizing two of the three metal d π orbitals.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, it exerts a relatively strong trans-influence or trans-effect, thus leading to metal-ligand bonds activated [11][12][13][14]. Special attention was paid to nitrosyl complexes [15][16][17][18][19][20]. Berke and his group have studied the chemistry of nitrosyl-substituted transition metal hydrides [21][22][23] in recent years such as trans-W(CO) 2 H(NO)(PR 3 ) 2 , Re(CO)H 2 (NO)(PR 3 ) 2 , MnH(NO) 2 (PR 3 ) 2 , ReH(NO) 2 (PR 3 ) 2 , and demonstrated that the nitrosyl ligand can activate the M-H bond and induce a quite strong hydridic polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Anionic carbene complexes are rare relative to neutral and cationic carbene complexes. Reactions of several anionic group VI carbene complexes have been reported during the past decade. Protonation at metal followed by hydride migration to a carbene ligand has been observed for the anionic Cp carbene complex [Cp(CO) 2 MoC(κ 2 -C,N-(CH 2 ) 3 NMe))] - ( 1 ), which resulted in the formation of the η 2 -alkylamine complex Cp(CO) 2 Mo(η 2 -C,N-CH(κ 2 -C,N-(CH 2 ) 3 NMe)) ( 2 ) (Scheme ) . A related migration was observed for the carbene complex Cp(CO) 2 (η 1 -C(O)Ph)WC(κ 2 -C,N-(CH 2 ) 3 NMe) ( 3 ), in which the benzoyl ligand migrates to the carbene ligand to form Cp(CO) 2 W(η 2 -C,N-C(κ 2 -C,N-(CH 2 ) 3 NMe)(C(O)Ph)) ( 4 ) (Scheme ) …”
Section: Introductionmentioning
confidence: 99%